Requirements determination in a community informatics project: An activity theory approach - (:unkn) unknown (SPRINGER-VERLAG BERLIN, 2006)
Requirements determination is arguably the most important phase of any system development project. This is due to the fact that the entire project is shaped according to the perceived or real requirements obtained in this phase. Although there is a wide body of literature on requirements engineering for IS development projects, there have been only a few attempts lately to theorize requirements determination for community informatics development. This article attempts to analyze the requirements determination efforts for a proposed community informatics project in Turkey by Activity Theory.
Keywords: SYSTEMS; DESIGN